RESPONSE OF GROWTH AND YIELD OF TWO VARIETY OF SOYBEAN (Glycine Max . ( L ) Merrill ) TO AVAILABLE SOIL WATER DEPLETION - Panalosa, Dody (The University of Lampung, 2015)
All this time, efforts to improve soybeanproductivity is still based onthe expansion of planting area (Badan PusatStatistik, 2013), but production is still declining. It is also influenced by the lack of understanding about thecultivation of soybeans and the price is less promising causing farmers are reluctant to plant soybeans. Thisresearch aims to investigate the response of the growth and productionof two varieties of soybean (Glycinemax.(L) Merrill) to some degree of available soil water depletion. This research was conducted at the Laboratory ofIntegrated Courses Faculty of Agriculture, University of Lampung, in May up to August 2014, using factorialdesign in a completely randomized designwith the first factor is depletion of groundwater available (P) which iscomposed of four levels of available soilwater depletion treatment (ATT) is the treatment P1 (0-20%),P2 (0-40%),P3 (0-60%), and P4 (0-80%) and the second factor, namely soybean varieties (V), which consists of varieties V1(Wilis) and V2 (Kaba), with three repetitions. Results were analyzed by F test at LSD further by 5%and 1% byusing Statistix8 Program. The results showed that the effect of the level of available soilwater depletionduring thevegetative stage and generative phase did not significantly affect plant growth and crop yield. The highestproduction yield andWilis varieties Kaba obtained at a rate of 0-40%thinning. Based on these values concludedthat to produce optimal production in both varieties can still bemaintained until the level of depletion of availablesoilwater content to 40%.Keyword : Available SoilWater,Depletions, Generative Phase, Vegetative Phase, Yield.